On the perils of racialized Chineseness: race, nation and entangled racisms in China and Southeast Asia. Issue 4 (12th March 2022) - Ang, Ien
ABSTRACT: This paper discusses how ideas of "race" and racial identification have, in different ways, been central in the construction of modern nation-states, both in East Asia and in postcolonial Southeast Asia, helping to entrench notions of racial difference as a fundamental element in nation-building. Processes of human racialization – and consequently, the homogenization of racialized identities and essentialization of human inequality – are thus persistent structuring devices that organize the workings of human societies. The paper focuses especially on the complex and contradictory ramifications of the racialization of "the Chinese" inside and outside of China, threatening to take on a perilous turn in the current era of China's rising global power and heightened Sinophobia.